Creativity in Deriving The Fermi-Dirac Equation Through STEAM Approaches - Fauzan Sulman; Lia Yuliati; Boby Yasman Purnama; Muhammad Reyza Arief Taqwa; Rizki Ananda (Berkala Ilmiah Pendidikan Fisika, 2022)
This research is motivated by statistical physics learning in deriving the Fermi-Dirac equation conceptually from lecturers to students or by rote and low creativity of students. This study aims to explore student learning creativity in deriving the Fermi-Dirac equation through the STEAM approach. This study uses a didactic design that includes the stages of prospective analysis, didactic metapedia analysis, and prospective re-analysis, which is applied to the sixth-semester physics tadris student of UIN Sulthan Thahah Saifuddin Jambi. The research instrument used is a description test and a non-test through observation sheets and interviews. The results showed that the implementation of STEAM could increase the creativity of statistical physics with an achievement level of 87% asking questions, 78% learning outcomes, 75% reflection, and 75% analysis on the material of the Fermi-Dirac equation by adhering to student activities starting with phenomena that are easy to digest with the realistic situation during online lectures, which shows that the STEAM approach is quite well used in deriving the Fermi-Dirac equation in the online statistical physics course.